Adsorption of metals from oil sands process water (OSPW) under natural pH by sludge-based Biochar/Chitosan composite. (15th April 2021) - Song, Junying; Messele, Selamawit Ashagre; Meng, Lingjun; Huang, Zhanbin; Gamal El-Din, Mohamed
Highlights: Sludge-based biochar/chitosan was used to remove metals from OSPW. The synthesized adsorbent exhibited superior efficiency for metals removal. Freundlich isotherm showed the best performance for modeling adsorption equilibrium. The adsorption process could be described using the pseudo second order model. Chemical adsorption might play the dominant role in the removal process. Abstract: Some metals in oil sands process water (OSPW) are potential threats to human health and the environment. Hence, the removal of excess metals from OSPW is of great significance. In this study, anaerobic sludge waste from a wastewater treatment plant, was reused to prepare sludge-based biochar. A Biochar/Chitosan (Biochar/CS) adsorbent with excellent removal efficiency for metals (Cr, Cu, Se and Pb) in real OSPW was prepared through a facile hydrothermal method. The structural properties of the synthesized Biochar/CS composite were characterized via X-ray diffraction (XRD), scanning electron microscopy (SEM) and Brunauer–Emmett–Teller (BET) method. This study reports for the first time the removal of metals from OSPW under natural pH using Biochar/CS adsorbent. The composite exhibited a higher removal efficiency towards Cr (83.9%), Cu (97.5%), Se (87.9%) and Pb (94.3%) when the initial concentrations of Cr, Cu, Se and Pb were 0.02914, 0.06185, 0.00800 and 0.00516 mg/L, respectively, at a dosage of 0.5 g/L, compared with biochar or chitosan alone. The possible adsorption mechanism was proposed, and the enhanced removal ability was due to the improved specific surface area and pore volume, which increased by about 20 and 14 times as compared with chitosan. Functional groups in the composite, such as –NH2, -OH and some oxygen containing groups, were also responsible for the enhanced removal ability, which also might be the reason for the better performance of the composite than biochar alone due to the lack of functional groups on the biochar. Moreover, the adsorption process was best modelled by the Freundlich model, pseudo second order and intraparticle diffusion kinetic models. The results indicated that chemical adsorption might play the dominant role in the removal process. Overall, the Biochar/CS composite would be a promising and effective adsorbent for metals removal, owing to its advantages of being cost-effective and environmentally friendly. Graphical abstract: Image, graphical abstract